Sosialisasi Penerapan Sila ke Dua Kemanusian yang Adil dan Beradab di MI Al-Misbah - Putri, Astian; Ali, Adlan; Fauziyah, Salwa; Satria, Maulana; Hakim, Muhammad Taufiqul; Kamil, Muhammad; Maulida, Putri Zahra; Setiadi, Aneza Putri; Aliyah, Rosmatun; Sri, Neng; Ikyan, Adzka; Herdiana, Dian (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
The second principle of Pancasila, "Just and Civilized Humanity", emphasizes the values of humanity that respect and appreciate every individual. In this activity, we teach and introduce MI Al-Misbah children about the application of manners towards parents, friends, and knowledge or books. We also introduce students to the negative impacts of bullying towards friends. Which will result in long-term trauma, and can be dealt with in Indonesian law. After the speaker, we carried out a game activity with prizes with the aim of encouraging children to answer questions given by the material teachers. We hope that children can follow and apply the material that we have provided.